Are Transbronchial Cryobiopsies Ready for Prime Time?: A Systematic Review and Meta-Analysis. Issue 1 (January 2019) - Sethi, Jaskaran; Ali, Muhammad S.; Mohananey, Divyanshu; Nanchal, Rahul; Maldonado, Fabien; Musani, Ali
Abstract : Background: There is a lack of consensus regarding the yield and safety of transbronchial cryobiopsies for diagnosing diffuse parenchymal lung diseases (DPLD). The purpose of this study was to perform a systematic review and meta-analysis assessing the diagnostic yield and safety profile of transbronchial cryobiopsies in DPLD. Methods: A literature search of MEDLINE, EMBASE databases, and Google Scholar was performed in August 2017. The quality of included studies was assessed using Quality Assessment, Data Abstraction and Synthesis-2 tool. Meta-analysis was performed using MedCalc (version 17.2). Inverse variance weighting was used to aggregate diagnostic yield proportions across studies, with the number of subjects in each study representing its weight. Random effects model was used when significant heterogeneity was observed ( I 2 >40%). Results: A total of 31 studies were included in the review. Of these, 27 studies with 1443 patients reported data on the performance of cryobiopsies for diagnosing DPLD. The diagnostic yield was 72.9% [95% confidence interval (CI), 67.9%-77.7%]. The pooled mean specimen size obtained by cryobiopsies was 23.4 mm 2 (95% CI, 9.6-37.3 mm 2 ). The overall complication rate was 23.1% with bleeding and pneumothoraces being the most commonly reported complications. The incidence of significant bleeding was 14.2% (95% CI, 7.9%-21.9%), whereas pneumothorax was seen in 9.4% (95% CI, 6.7%-12.5%) of patients. Overall reported mortality was 0.3%. Conclusion: Our meta-analysis shows that cryobiopsies have a good diagnostic yield but a significant risk for complications. Cryobiopsy outcomes vary markedly among different centers. Further research is needed to standardize the procedure and improve its safety profile. Abstract : Supplemental Digital Content is available in the text.